Material modification and characterization based on small molecule diffusion - Coceancigh, Herman (Kansas State University, 2020)
This dissertation shows the use of small molecule diffusion as a method to control the modification inside poly(ethylene terephthalate) (PET) track-etched membrane pores and to unveil unique qualities of polystyrene-block-poly(ethylene oxide) (PS-b-PEO). The first project took advantage of electrochemical control of the diffusion length of a Cu (I) catalyst for azide-alkyne cycloaddition click reaction. By controlling the diffusion time of the catalyst generated at an underlying electrode, the modification along 1 µm pores in a PET track-etched membrane could be controlled. The complex of Cu(I) and tris[(1-benzyl-1H-1,2,3-triazol-4-yl)methyl]amine (TBTA) was used as the catalyst for the click reaction between an azide-tagged fluorescent dye and an alkyne group immobilized on the inner surface of the pore. The resulting surface modification was assessed by fluorescence microscopy. This approach was applicable to the asymmetric modification of cylindrical pores with two different fluorescent dyes in the opposite directions and for the selective visualization of the tip and base opening of conical pores. The cross-sectional fluorescence profile of the modified pores confirmed an increase in the surface modification yield for the longer duration of Cu(I) production. The second project measured the diffusion of sulforhodamine B (SRB) inside the PEO microdomains of thin PS-b-PEO films. The diffusion of SRB revealed the unique swelling properties of thin PS-b-PEO films under ethanol or water vapor. Specifically, the effects of swelling of the PEO microdomains were studied using spectroscopy ellipsometry (SE), single molecule tracking (SMT) and fluorescence correlation spectroscopy (FCS). Results for PS-b-PEO were compared with those for a polystyrene homopolymer (hPS[subscript 16.4]) and poly(ethylene oxide) homopolymers (hPEO[subscript 12.5] and hPEO[subscript 3.8]) to confirm the unique swelling behavior. The results showed that while ethanol vapor could swell neither hPS[subscript 16.4] nor hPEO[subscript 12.5] thin films, it could swell the PEO microdomains. Water vapor could swell both the PEO microdomains and the hPEO[subscript 12.5]. SE and SMT videos confirmed the swelling of the PEO microdomains. The immutability of hPS[subscript 16.4] and the PS microdomains of PS-b-PEO under these solvent vapors was confirmed from the fluorescence emission of solvatochromic Nile Red (NR) using two-color wide-field microscopy. Furthermore, FCS was used to quantitatively assess swelling-induced changes in diffusion behavior of SRB in PEO microdomains. FCS results showed that hPEO[subscript 12.5] was not swollen by ethanol vapor but smaller PEO microdomains were swollen more significantly, the latter of which was suggested by the SRB diffusion. These two projects strongly relied on the use of small molecule diffusion to control the length of pore surface modification and to verify the unique swelling of the PEO microdomains, respectively.
Keywords: PET track-etched membrane; Diffusion; Fluorescence microscopy; Poly(ethylene terephthalate); Polystyrene-block-poly(ethylene oxide)